Technical research of a new type of optical fibre with ultra-low-loss and large effective area - Di HAN; Hua XIAO; Yuan ZHONG; Xuegang LAO; Chao HAN (Dianxin kexue)
The technical solutions of double-cladding waveguide structure and pure SiO2core were taken,the G.654.E type ULA-130 fibre ultra-low-loss and large effective area was realized by F-doping design and optimization of the viscosity match between core and caldding.Then the study on various optical characteristics of the ULA-130 fibre was carried out,utilizing self-built optical fibre nonlinear coefficient measurement system and self-designed optical fibre macro-bending loss winding device,as well as the avaliable techniques.The attenuation coefficient,effective area and nonlinear coefficient at 1 550 nm of the ULA-130 fibre was 0.159 dB/km,133 μm2and 1.67×10-10W-1separately.According to the theoretical calculation and technical analysis,the ULA-130 fibre posseses excellent attenuation and nonlinear performance,which is applicable in high capacity,high bitrate and long-range optical backbone network system.Compared to conventional G.652.D fibre,the ULA-130 fibre could improve the optical singal-noise ration and the performance of transmission system dramatically.